Neuroimaging and the question of neurodegeneration in schizophrenia - Meyer-Lindenberg, Andreas (Progress in neurobiology, 2011)
Volume reductions in brain structures of patients with schizophrenia spectrum disorder (SSD) have repeatedly been found in voxel-based morphometry MRI studies. Hence, an underlying neurodegenerative etiological component of SSD is currently being discussed. In recent years, the imaging method of optical coherence tomography (OCT) has shown its potential in evaluating structural changes in the retina in patients with confirmed neurodegenerative disorders, providing a window into the brain. - Twenty-six patients with schizophrenia or schizoaffective disorder and 23 age- and sex-matched healthy controls were examined with the Heidelberg Spectralis OCT system to derive a single-layer analysis of both retinas. The segmentation of retinal layers was manually corrected to minimize artifacts and software imprecisions. - Compared to the control group, SSD patients showed reduced thickness and volume measurements for nearly all retinal layers, and these differences reached significance for macular volume, macular thickness, retinal nerve fiber layer (RNFL) and inner nucleiform layer (INL). Furthermore, a significant correlation between the duration of illness and the total volume of the RNFL was found. - Our OCT measurements demonstrate reduced single retinal layer thickness in patients with SSD. In the context of the MRI volume changes, our results provide further evidence that structural changes seen in the brain of patients are also observable in the retina, potentially allowing further insights into the different components of the nervous system that are altered in this highly etiologically complex disorder. - Schizophrenia is a complex neuropsychiatric illness with marked sex differences. Women have later onset and lesser symptoms, which has led to the hypothesis that estrogens are protective in schizophrenia. Cognitive dysfunction is a hallmark of the disease and the symptom most correlated with functional outcome. Here we describe a number of mechanisms by which estrogens may be therapeutic in schizophrenia, with a focus on cognitive symptoms. We review the relationship between estrogens and brain derived neurotrophic factor, neuroinflammation, NMDA receptors, GABA receptors, and luteinizing hormone. Exploring these pathways may enable novel treatments for schizophrenia and a greater understanding of this devastating disease. - Thioredoxin is a serum antioxidant that has been investigated in the etiology of schizophrenia. The aim of this study is investigating the relationship between serum thioredoxin levels and cognitive functions in acute psychotic episode and remission state patients with schizophrenia; and examining whether there were differences between patients using clozapine and other atypical antipsychotics; including risperidone, olanzapine and amisulpride. This research was performed in schizophrenia patients hospitalized with acute psychotic episode (n=57), reevaluated patients after the initiation of treatment (mean 16 weeks) (n=46), and healthy controls (n=41). Positive and Negative Syndrome Scale, Clinic Global Impressions Scale, Neuropsychologic test battery to assess cognitive performance, and serum thioredoxin levels measured by ELISA were used in this research. Serum thioredoxin levels were highest in acute psychotic episode, lower in the remission state and the lowest in healthy controls. Significant correlation has been established between serum thioredoxin levels and Trail Making Test-A performance in remission state patients. In conclusion, serum thioredoxin levels were increased in acute psychotic episode and decreased in remission state, and its relationship with attention is worth to consider in schizophrenia patients. - Findings from neuroimaging studies in patients with schizophrenia suggest widespread structural changes although the mechanisms through which these changes occur are currently unknown. Glutamatergic activity appears to be increased in the early phases of schizophrenia and may contribute to these structural alterations through an excitotoxic effect. The primary aim of this review was to describe the possible role of glutamate-mediated excitotoxicity in explaining the presence of neuroanatomical changes within schizophrenia. A Medline® literature search was conducted, identifying English language studies on the topic of glutamate-mediated excitotoxicity in schizophrenia, using the terms “schizophreni⁎” and “glutam⁎” and ((“MRS” or “MRI” or “magnetic resonance”) or (“computed tomography” or “CT”)). Studies concomitantly investigating glutamatergic activity and brain structure in patients with schizophrenia were included. Results are discussed in the context of findings from preclinical studies. Seven studies were identified that met the inclusion criteria. These studies provide inconclusive support for the role of glutamate-mediated excitotoxicity in the occurrence of structural changes within schizophrenia, with the caveat that there is a paucity of human studies investigating this topic. Preclinical data suggest that an excitotoxic effect may occur as a result of a paradoxical increase in glutamatergic activity following N-methyl-d-aspartate receptor hypofunction. Based on animal literature, glutamate-mediated excitotoxicity may account for certain structural changes present in schizophrenia, but additional human studies are required to substantiate these findings. Future studies should adopt a longitudinal design and employ magnetic resonance imaging techniques to investigate whether an association between glutamatergic activity and structural changes exists in patients with schizophrenia. - Several diffusion tensor imaging (DTI) studies have reported disturbed white matter integrity in various brain regions in patients with schizophrenia, whereas only a few studied the effect of antipsychotics on DTI measures. The aim of this study was to investigate the effect of 12 weeks of clozapine treatment on DTI findings in patients with schizophrenia, and to compare the findings with those in unaffected controls. The study included 16 patients with schizophrenia who were assessed with the Positive and Negative Syndrome Scale, a neurocognitive test battery, and DTI at baseline and 12 weeks after the initiation of clozapine treatment. Eight unaffected controls were assessed once with the neurocognitive test battery and DTI. Voxel-wise analysis of DTI data was performed via tract-based spatial statistics (TBSS). Compared with the control group, the patient group exhibited lower fractional anisotropy (FA) in 16 brain regions, including the bilateral superior longitudinal fasciculi, inferior fronto-occipital fasciculi, superior and inferior parietal lobules, cingulate bundles, cerebellum, middle cerebellar peduncles, and left inferior longitudinal fasciculus, whereas the patients had higher FA in six regions, including the right parahippocampus, left anterior thalamic radiation, and right posterior limb of the internal capsule before clozapine treatment. After 12 weeks of treatment with clozapine, white matter FA was increased in widespread brain regions. In two of the regions where FA had initially been lower in patients compared with controls (left inferior fronto-occipital fasciculus and superior parietal lobule), clozapine appeared to increase FA. An improvement in semantic fluency was correlated with the increase in FA value in the left inferior fronto-occipital fasciculus. An increase in FA following 12 weeks of treatment with clozapine suggests that this treatment alters white matter microstructural integrity in patients with schizophrenia previously treated with typical and/or atypical antipsychotics and, in some locations, reverses a previous deficit. - Variation in the CACNA1C gene has consistently been associated with psychosis in genome wide association studies. We have previously shown in a sample of n = 110 healthy subjects that carriers of the CACNA1C rs1006737 risk variant exhibit hippocampal and perigenual anterior cingulate dysfunction (pgACC) during episodic memory recall. Here, we aimed to replicate our results, by testing for the effects of the rs1006737 risk variant in a new large cohort of healthy controls. We furthermore sought to refine these results by identifying the impact of a CACNA1C specific, gene-wide risk score in the absence of clinical pathology. - An independent sample of 179 healthy subjects genotyped for rs1006737 underwent functional magnetic resonance imaging (fMRI) while performing an associative episodic memory task and underwent psychological testing similar to the discovery sample. The effect of gene-wide risk scores was analyzed in the combined sample of 289 subjects. - We replicated our discovery findings of hippocampal and pgACC dysfunction in carriers of the rs1006737 risk variant. Additionally, we observed diminished activation of the dorsolateral prefrontal cortex, in the replication sample. Our replicated results as well as this new effect were also o...